Development of an Anisotropically Organized Brain dECM Hydrogel-Based 3D Neuronal Culture Platform for Recapitulating the Brain Microenvironment in Vivo - Seo, Yoojin; Jeong, Sohyeon; Chung, Justin Jihong; Kim, Soo Hyun; Choi, Nakwon; Jung, Youngmee (AMER CHEMICAL SOC, 2020)
To mimic the brain tissue microenvironment in vitro, the biological and structural properties of the utilized system must be similar to those of the native brain in the microenvironment in vivo. To promote the bioactive (biological) properties of matrix hydrogels, we used the decellularized extracellular matrix (dECM) of porcine brain, which was found to enhance neuronal differentiation/outgrowth and neuron-to-brain dECM interactions. To implement the desired structural properties, we aligned microfibrils within a composite hydrogel mixed with the brain dECM and collagen I, with or without encapsulated neurons, by the stretching and releasing of a hydrogel-based chip. We then tested the ability of the aligned brain dECM hydrogel-based three-dimensional (3D) culture platform to mimic the in vivo brain microenvironment. We found that dECM-containing gels harbored brain-derived ECM proteins, including collagen I, collagen IV, laminin, and various cytokines, and that neurons incubated in these gels exhibited enhanced neurite outgrowth and development compared to those incubated in collagen gel (dECM 0 mg/mL). We evaluated the surface morphology and mechanical properties of the hydrogel with and without the brain dECM and found that their encapsulated neurons showed similar levels of cell viability. We then used a mechanical process to align the composite dECM hydrogel, conferring the desired structural properties to our system. Together, our results suggest that our newly developed brain dECM-based 3D culture platform could potentially be further developed for use in drug screening.
Keywords: NEURAL STEM-CELLS; NEURITE OUTGROWTH; HIPPOCAMPAL-NEURONS; CORTICAL-NEURONS; FETUIN-A; MATRIX; GROWTH; DIFFERENTIATION; SPECIFICATION; INDUCTION